Metal Dihydrazide Precursors as Building Blocks for New Macrocyclic Architechtures with Tetradentate Octaaza Dibasic Ligands - RAI, H.C.; KUMAR, RAJEEV; KUMAR, ANIL; Priyanka, (Asian Journal of Chemistry, 2010)
A series of 16-membered macrocyclic complexes of cobalt(II) and nickel(II) of the type [M(H2Cy1-4)] have been synthesized and characterized on the basis of spectral, magnetic and conductivity studies. The macrocyclic ligands H4Cy1-4 are tetrabasic having four imido hydrogen but behave in a dibasic manner. Out of eight nitrogens, four imido and four imino, ligands utilize four imido nitrogens for square planar coordination forming four 7:5:7:5 chelate rings giving rise to a 16 membered macrocyclic framework. The red coloured nickel(II) complexes are diamagnetic in nature, whereas cobalt(II) complexes with chocolate brown colour are of low spin type. Low molar conductivity values in the range 3-7 ohm-1 cm2 mol-1 suggest complexes to be non-electrolytic in nature. High dilute conditions generally employed in the synthesis of macrocyclic complexes in order to dispense with polymerization reaction have been avoided in the present study and advantage of orientation effect has been taken to have high yield.